Diagnosis and Treatment Modalities for Aberrations of Normal Development and Involution of the Breast: A Clinical Study - Salman Raghib, Sheik; Lenka, Biswadeep; Afzal, Tajma (Journal of Neonatal Surgery, 2025)
Background: Benign breast disorders are frequent conditions that occur as a result of aberrations in normal development and involution (ANDI) of breast tissue. It is crucial to know their clinical presentation, diagnosis, and treatment modalities for proper management. The purpose of this study is to assess the spectrum of benign breast diseases, their diagnostic methods, and treatment results with the ANDI classification. Methods: Prospective observational study was done on 250 female patients with benign breast disorders. Clinical assessment, imaging (ultrasonography and mammography), and fine-needle aspiration cytology (FNAC) were used for diagnosis. Conservative treatment, surgical excision, and antibiotic therapy were used as and when indicated for management. Patients were followed up for six months to evaluate treatment response and rates of recurrence. Results: The most frequent benign breast condition was fibroadenoma (38.0%), followed by fibrocystic changes (22.4%) and mastitis/abscess (12.8%). Duct ectasia was seen in 8.4%. FNAC was accurate in 92.4%, and ultrasonography was the most common imaging technique used. Conservative treatment succeeded in 64.8% of patients, while surgical excision was necessary in 35.2%. Symptoms resolved in 89.6% of patients, and recurrence was 6.8%. Conclusion: Most benign breast disorders occur in young and middle-aged women, with the most common diagnosis being fibroadenoma. ANDI classification offers an organized method of differentiation between physiological variations and pathological conditions. Early diagnosis and tailored treatment plans lead to beneficial clinical results with minimal recurrence.